General arrangement and working detail drawings and costing for steel framed structures on a microcomputer - Supachai Prechaterasat; Brotton, Derick M.; Nishino, Fumio; Carmichael, D.G.; Government of The Netherlands (Bangkok : Asian Institute of Technology, 1985)
A microcomputer package which had previously been develop for the design of a planar steel frame structure with the adoption of the Australian Standards Code AS1250-1975 and relevant design codes has been adapted. The analysis program package, MICROFEAP, has also been incorporated with some modifications to deal automatically with three load combinations. The package has essentially been arranged to be of more practical use for the designer. The data input process has been simplified and separated from the design parts. With the incorporation to the new version of the MICROFEAP package, the analysis time has been reduced guite significantly. The design of the bolted connections has been provided for the joints of the building. The use of the plotter machine to generate the drawings i.e., was also included. Finally, the required materials can be determined and hence the costing can be estimated using the given cost library.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Structural frames -- Models; Microcomputers